FATWA MUI TENTANG PENGURUSAN JENAZAH MUSLIM YANG TERINFEKSI COVID-19 DITINJAU DARI PERSPEKTIF MAZHAB SYAFI’I - Ayyub Subandi (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed at analyzing the fatwa of the Indonesian Council of Ulama (MUI) regarding the management of Muslim dead body infected with Covid-19 regarding the Shafi'i School. This research used descriptive qualitative approach with content analysis techniques and library research. The results showed that the fatwa of MUI regarding the management of Muslim dead body infected with Covid-19 in general had been conducted in accordance with the established fiqh of Shafi'i School, even based on the agreement of the four schools.